2022
DOI: 10.1155/2022/7218113
|View full text |Cite|
|
Sign up to set email alerts
|

Internet of Medical Things (IoMT)-Based Smart Healthcare System: Trends and Progress

Abstract: Internet of Medical Thing (IoMT) is the most emerging era of the Internet of Thing (IoT), which is exponentially gaining researchers’ attention with every passing day because of its wide applicability in Smart Healthcare systems (SHS). Because of the current pandemic situation, it is highly risky for an individual to visit the doctor for every small problem. Hence, using IoMT devices, we can easily monitor our day-to-day health records, and thereby initial precautions can be taken on our own. IoMT is playing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 96 publications
0
38
0
Order By: Relevance
“…Image segmentation refers to the techniques of dividing an image into different regions. The most effective method to analyze anatomical structure in medical is “region growing method” [ 42 , 43 ]. But it does not give proper and more accurate results if it directly applies to the input images that are having noisy and low contrast.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Image segmentation refers to the techniques of dividing an image into different regions. The most effective method to analyze anatomical structure in medical is “region growing method” [ 42 , 43 ]. But it does not give proper and more accurate results if it directly applies to the input images that are having noisy and low contrast.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Medical image encryption has become mandatory with the enhancement of cloud services and the Internet of Medical Things (IoMT) in 2022 [18]. For this reason, the authors suggested a 3D chaotic map system to protect the medical images and accomplish the best results.…”
Section: Related Workmentioning
confidence: 99%
“…The model makes use of both symmetric and uneven encryption calculation (AES and ECC) to enhance information security against intruders, preventing illegal access to natural resources, improving privacy and time taken to perform cryptographic tasks, and further developing the trust level of the client in the cloud and accelerating the use of more modest keys of ECC in the cryptographic interaction. Table 1 represents the comparative analysis of related work in detail papers [14][15][16][17][18][19][20] Table 1: Comparative analysis of related work Refs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenging applications are conceived, such as recovery from paralysis, which would need the communication among implants for the exchange of information inside/outside body. For these scenarios it is necessary to develop body-centric architectures based on both intranet and Internet of Medical Things (IoMT) [2], [3].…”
Section: Introductionmentioning
confidence: 99%